Costimulatory checkpoint SLAMF8 is an independent prognosis factor in glioma. (13th August 2018) - Zou, Cun‐Yi; Guan, Ge‐Fei; Zhu, Chen; Liu, Tian‐Qi; Guo, Qing; Cheng, Wen; Wu, An‐Hua
Abstract: Aims: Immune checkpoint blockade has made breakthroughs in immunotherapy for glioma. However, current immunotherapy has therapeutic benefits only in a subset of patients and accompanied by immune‐related side effects. SLAMF8 is a costimulatory molecule that affects the activation of macrophages in inflammation. The study of SLAMF8 may provide new information for immunological research and treatment of glioma. Methods: CGGA and TCGA cohorts of 946 patients with RNA sequencing data and full clinical information were analyzed using R language and GraphPad Prism 7. Results: SLAMF8 was overexpressed along with malignancy progression and was a biomarker of mesenchymal subtype. As an independent prognostic factor, high SLAMF8 conferred reduced overall survival and chemotherapy resistance. SLAMF8 implied lower proportion of cancer cells along with increasing enrichment of monocytic lineage, myeloid dendritic cells. Functional analysis showed higher SLAMF8 indicated activation of antigen processing and presenting and the IFN‐γ/TNF/TLR‐mediated signaling. Meanwhile, coexpressing with classical checkpoint SLAMF8 aggravated immunosuppression and enhanced inflammation response. Conclusion: Our study highlighted the important role of SLAMF8 in malignancy progression, shortened survival, and immune disorders. Further research on SLAMF8 in immunosuppression and inflammation response to glioma cells could aid immunotherapy for glioma.